PENGEMBANGAN KOTA KREATIF DI KOTA BAUBAU - Arlita Aristianingsih Jufra; Syamsul Anam; Muhammad Irfan Basri; Muhammad Imran (Universitas Muhammadiyah Kendari, 2021)
The development of a creative city can not be separated from the potential of the diversity of cultural, artistic and human resources derived from the value of exchange rates can encourage the expansion of insight and creativity. In terms of development, the creative city can be further enabled through the reshaping of the city (reshape the design of the city in terms of development, improvement, community participation), presents a view of urban (provide physical intervention and view inspiring), the marriage of the old and new (the goal is to decorate an attractive city and as a city that attracts and as a landmark and as a city (also). The activity of the Master Plan for the development of Creative Cities in Baubau detained for 2 months of October until 2020 December. The Masterplan has been set up guide, direction, policy, and the things that draws on the development of creative cities in Baubau will be adjusted and aligned with the RPJMD and plan the construction of the other in Baubau. The identification of the conditions and characteristics of the creative economy is done by determining the respondents were participants from each sub-sector of the creative economy in Baubau. The results of the determination of the results of the respondents as many as 143 respondents were divided into 11 sub-sectors of the creative economy in Baubau covering fashion, culinary art, handicrafts, and others (Architecture, Design, App, Design, Design, Film, interior, and music).